Clinical Meaning of Ascites in Patients with Endomyocardial Fibrosis - Barretto,Antonio Carlos Pereira (2002)
OBJECTIVE: To evaluate the clinical meaning of ascites and the main features of patients with ascites and endomyocardial fibrosis. METHODS: We studied 166 patients with endomyocardial fibrosis (mean age 37 years, 114 women) treated over the last 20 years. Ventriculography findings, surgery or necropsy confirmed the diagnosis in all patients. Most patients belonged to New York Heart Association Functional Class III/IV (134, 83.7%). Eighty-one (50.6%) had biventricular, 28 (17.5%) had right ventricular, and 51 (31.8%) had left ventricular involvement. During follow-up, 56 patients died. RESULTS: Ascites was present in 67 (41.8%) patients, and right ventricular involvement was present in 59 (88%). In the comparison between patients with or without ascites, those with ascites had higher mortality (49.2% and 24.7%, respectively). Patients with ascites had a higher incidence of edema (95% vs. 43%), hepatomegaly (5.8cm vs. 4.1cm), mean right atrium pressure (19.3 vs. 12mmHg), and final right ventricle diastolic pressure (18.7 vs. 12.9mmHg). Also, patients with ascites had a longer history of illness (5.1 and 3.9 years, respectively) and had atrial fibrillation more frequently (44.7% vs. 30.1%). CONCLUSION: Ascites was observed in less than 50% of cases of endomyocardial fibrosis and was associated with greater involvement of the right ventricle and with a longer duration of the disease, thus being a characteristic of a worse prognosis.